Industrial Process Improvement by Automation and Robotics - Campilho, Raul D. S. G.; Silva, Francisco J. G. (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The pursuit of industrial process improvement has been a continuous task in modern manufacturing and production. The confluence of automation and robotics has not only revolutionized manufacturing processes but has also redefined the benchmarks of efficiency, precision, and adaptability in various industries. This reprint, "Industrial Process Improvement by Automation and Robotics", is a comprehensive collection of research papers, each chapter delving into distinct facets of the integration of automation and robotics to enhance industrial processes across diverse applications. The compilation of fourteen chapters covers a broad spectrum of topics, addressing the latest technological advancements and innovative methodologies employed in industrial automation.The primary aim of this reprint is to serve as a compendium for researchers, engineers, industrial practitioners, and academicians actively involved or interested in the domains of automation, robotics, and industrial process improvement. The multidisciplinary approach of these chapters caters to a diverse audience seeking in-depth knowledge, innovative strategies, and insightful perspectives in this evolving field.